Persistent residual contamination in endoscope channels; a fluorescence epimicroscopy study - Hervé, Rodolphe C.; Keevil, Charles W. (Endoscopy, 2016)
Background and study aims: The increasing demand for endoscopic procedures poses new contamination challenges, given developing antimicrobial resistance worldwide and potential viral or prion diseases in populations at risk. We examined working channels from reusable luminal endoscopes used in recent years. Methods: Very sensitive fluorescence epimicroscopy was used to examine working channels from 6 decommissioned and 6 factory-new channels, as received, or following spiking and washing in the laboratory.Results: After a single contamination and wash test cycle, new channels retained approximately 75 pg/mm2 of proteins; through 7 subsequent cycles residual proteins fluctuated between 25 and 75 pg/mm2. Decommissioned channels harbored 1 – 4 µg of proteins each, except in one gastroscope (33 µg), including up to 2 % amyloid proteins except in one gastroscope and one sigmoidoscope (with over 80 %); lumens showed wearing with established abraded biofilms in 3 cases. After spiking with scrapie-infected blood components and washing, residual protein levels in new channels varied following standard (17.23 pg/mm2), duplicated (2.39 pg/mm2) or extended (11.3 pg/mm2) washing; no changes were measured among the long-established contamination in old channels. Conclusions: Our observations suggest that wear effects in endoscope lumens may contribute to the adsorption of proteins, thus facilitating retention and survival of bacteria. As demonstrated by recent outbreaks worldwide despite recommended reprocessing, the development of antimicrobial-resistant bacterial strains, and the estimated prevalence of variant Creutzfeldt-Jakob disease (vCJD) in the UK particularly, combined with increasing demand for endoscopic procedures, call for sustained precautions and improved methods for the reprocessing of nonautoclavable, reusable surgical instruments.